WASTE ELECTRICAL AND ELECTRONIC EQUIPMENT FRAMEWORK LEGISLATION AND MANAGEMENT SYSTEM IN EUROPE - Maria-Loredana NICOLESCU (Challenges of the Knowledge Society)
Waste electrical and electronic equipment (WEEE) has become one of the most significant waste streams due to the increasing amounts and environmental impact. It is very important to know how to manage the WEEE quantities, what laws are in force in this field and what policies are available to apply. This paper presents the e-waste legislation and management system from some of the European countries, as examples. The hierarchy of the management systems is presented according to the framework Directive and legislative approaches. There are also shown the "take-back" policy, the "polluter pays" principle and the "extended producer responsibility" principle. The goal of this research is to highlight the WEEE framework legislation in Europe and to present the EU policies for the WEEE management system.